Effect of remote ischaemic preconditioning on walking in people with multiple sclerosis: double-blind randomised controlled trial - Chotiyarnwong, Chayaporn (BMJ Neurol Open, 2020)
BACKGROUND: Remote ischaemic preconditioning (RIPC) is the exposure of body parts to brief periods of circulatory occlusion and reperfusion. Recent studies have also shown that RIPC can improve exercise performance in healthy individuals. OBJECTIVE: This study aimed to assess the effect of RIPC on walking in people with multiple sclerosis (MS). METHODS: This was a double-blind randomised controlled clinical trial. We used three cycles of RIPC delivered by occluding the upper arm with a blood pressure (BP) cuff inflated to a pressure of 30 mm Hg above the systolic BP. In patients in the sham intervention group, the BP cuff was inflated only to 30 mm Hg below diastolic BP. Outcome measures included the Six-Minute Walk Test (6MWT), gait speed, the Borg rate of perceived exertion (RPE) scale, the tolerability of the RIPC using a Numerical Rating Scale for discomfort from 0 to 10, and adverse events. We identified responders meeting the minimal clinically important difference (MCID) established in the literature in each group. RESULTS: Seventy-five participants completed the study (RIPC: 38 and Sham: 37). The distance walked during the 6MWT improved by 1.9% in the sham group and 5.7% in the RIPC group (p=0.012). The number of responders meeting MCID criteria in the RIPC group was significantly greater compared with the sham intervention group. No serious adverse events occurred. CONCLUSION: Single cycle of RIPC resulted in immediate improvement in walking distances during 6MWT in people with MS. TRIAL REGISTRATION NUMBERS: NCT03153553